POLA DISTRIBUSI KOMODITAS KENTANG DI KABUPATEN BANDUNG, JAWA BARAT - Agustian, Adang; Mayrowani, Henny (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2008)
The study was conducted in Bandung District, West Java on 2005. Primary data were collected through interview with potatoâs farmers (who grow Granola variety and Atlantic variety) and potatoâs trader. Method of analysis is quantitative and qualitative analysis. The results of the study are as follow: (1) There are two kinds of marketing pattern of potato in West Java: (a) Marketing pattern of Granola variety which is distributed to several market especially central market. Majority of Granola variety is for household consumption; and (b) Partnership pattern between farmerâs group or farmers with PT Indofood FM for Atlantic variety. Most of this variety is used as a raw material for food processing industries; (2) Most of potatoâs farmers sell their product to village collectors, and potatoâs farmers who have large scale of potatoâs farm can directly sell to district traders and central market. (3) Atlantic variety were distributed through Farmerâs Group to Partner Company.